1996
DOI: 10.1002/eji.1830260841
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of numerous delivery systems for the induction of cytotoxic T lymphocytes by immunization

Abstract: A variety of vaccine delivery systems including peptides with various adjuvants, recombinant particles, live recombinant viruses and bacteria and plasmid DNA were tested for their ability to induce CD8+ cytotoxic T lymphocytes (CTL) against a well-defined epitope (amino acids 252-260) from the circumsporozoite (CS) protein of Plasmodium berghei. We compared routes of immunization that would be applicable for the administration of a malaria vaccine in humans. The majority of these vaccines did not induce high C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 51 publications
(11 reference statements)
3
47
0
Order By: Relevance
“…VLPs have also been proven to be potent CTL inducers compared with other vectors (21)(22)(23)(24). A study of PPV-VLPs immunization showed a safe and efficient strategy to induce CTLs and stimulate antiviral immunity in a CD4-independent manner (22).…”
Section: O Ne Of the Major Effects During The Course Of Hiv Infectionmentioning
confidence: 99%
“…VLPs have also been proven to be potent CTL inducers compared with other vectors (21)(22)(23)(24). A study of PPV-VLPs immunization showed a safe and efficient strategy to induce CTLs and stimulate antiviral immunity in a CD4-independent manner (22).…”
Section: O Ne Of the Major Effects During The Course Of Hiv Infectionmentioning
confidence: 99%
“…However, high cell densities of responding T cells by sensitization either in vivo or in vitro with a short peptide could not easily be achieved , Valmori et al 1994, Allsopp et al 1996.…”
Section: Induction Of Cd8 + T Cells Using Synthetic Non-infective Immentioning
confidence: 99%
“…Immunization with Ty-VLP carrying a CD8 + T cell epitope of the P. berghei CS protein (TyPb) resulted in an immune response (Allsopp et al 1996). This study compared four adjuvants designed for the use with peptide, lipopeptides, recombinant salmonella, vaccinia virus and an attenuated vaccinia, plasmid DNA and Ty-VLPs.…”
Section: Induction Of Cd8 + T Cells Using Synthetic Non-infective Immentioning
confidence: 99%
“…Sterile protection against sporozoite challenge can be transferred to naïve mice by CSP-specific CD8 + T cells [15][16][17][18]. There are several experimental vaccines described that successfully induce CSP-specific CD8 + T cells [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Sterile protection against sporozoite challenge can be transferred to naïve mice by CSP-specific CD8 + T cells [15][16][17][18]. There are several experimental vaccines described that successfully induce CSP-specific CD8 + T cells [19][20][21][22].In the present study we employed our previously described heterologous prime/boost vaccination strategy that is based on the induction of CD8 + T cells recognising a CSP-derived epitope of Plasmodium berghei presented by MHC class I [23]. Primary immunization is achieved with recombinant Salmonella.…”
mentioning
confidence: 99%